Researches on obtaining composite materials to be used in manufacturing brake pads. Issue 1 (January 2016) - Socalici, A; Pascu, L; Ardelean, E; Popa, E
Abstract: The paper presents the laboratory experiments and results meant for obtaining composite materials to be used in manufacturing brake pads for the drive and driven rolling stock. Six samples of composite material have been designed and obtained; each of them has been assessed in terms of tribological behavior using a tribotester and using the friction and wear parameters. Also, determinations have been made on the influence of the material factors and of the main parameters of the work conditions upon the tribological characteristics of the samples under tests and upon the processes that are going on in the superficial strata.